Artificial Intelligence for Arabic Lessons Will it Helps Teachers? - Agustina, Annisa; Cakmak, Fidel; Benzehaf, Bouchaib (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
This study aims to determine whether artificial intelligence for learning Arabic can help teachers. The method used by the researcher is a survey method from previous research, which also discusses artificial intelligence. Artificial intelligence can help teachers, especially in Arabic subjects. However, although it can help teachers learn Arabic, it still cannot replace the role of a teacher who teaches directly or face to face. Because Arabic is one of the subjects that teach all or everything related to language, experts are needed to teach it. So with the existence of artificial intelligence, teachers can be helped but not even though they are not optimal. No matter how well the program is designed, it cannot replace the teacher's position as an expert in science. The nature of the computer program is only as a tool, not as a transmitter of knowledge as a whole like a teacher. Technological advances are beneficial or can warn the teacher's work in certain areas. It is hoped that future researchers can use this research as reference material with this research.